Ultrafast high-temperature sintering of barium titanate ceramics with colossal dielectric constants - Reavley, Matthew Jun-Hui (2022)
Application of Ultrafast High-temperature Sintering (UHS) technique to rapidly densify barium titanate ceramics has been explored for the first time. Bulk ceramic with ~94% density was obtained by UHS at ~1340 °C for 60 seconds. The densification process was accompanied with progressive sample discolouration from light to dark grey. Further analysis indicates that oxygen vacancy and its associated Ti-rich phase Ba4Ti12O27 are present in the ceramics. Their roles in ultrafast densification and sample discoloration are discussed. Due to the presence of oxygen vacancies, the UHSed ceramics generally exhibit a colossal dielectric constant of ~ 15–30k at 1 kHz, with dielectric loss of ~0.07–0.10, while the ceramics without oxygen vacancy retain a dielectric constant of ~3000–6000 and dielectric loss of ~ 0.06 at 1 kHz which are comparable to that of the conventionally sintered ceramics. Furthermore, the challenges in applying UHS to sinter thick BT ceramics are discussed, aided by thermal simulations.